Automating Installation of the Integrating Biology and the Bedside (i2b2) Platform. (1st June 2018) - Wagholikar, Kavishwar B; Mendis, Michael; Dessai, Pralav; Sanz, Javier; Law, Sindy; Gilson, Micheal; Sanders, Stephan; Vangala, Mahesh; Bell, Douglas S; Murphy, Shawn N
Informatics for Integrating Biology and the Bedside (i2b2) is an open source clinical data analytics platform used at more than 150 institutions for querying patient data. An i2b2 installation (called hive) comprises several i2b2 cells that provide different functionalities. Given the complex architecture of i2b2 installation, creating a working installation of the platform is challenging for new users. This is despite the availability of extensive documentation for i2b2 and access to a large and active mailing list community of i2b2 users. To address this problem, we have created an automated installation package, called i2b2-quickstart, which automatically downloads the latest i2b2 source code and dependencies, and compiles and configures the i2b2 cells to create a functional i2b2 hive installation. This package will serve as a convenient starting point and reference implementation that will facilitate researchers in the installation and exploration of the i2b2 platform.